2022
DOI: 10.1093/cid/ciac827
|View full text |Cite
|
Sign up to set email alerts
|

Limited Weight Impact After Switching From Boosted Protease Inhibitors to Dolutegravir in Persons With Human Immunodeficiency Virus With High Cardiovascular Risk: A Post Hoc Analysis of the 96-Week NEAT-022 Randomized Trial

Abstract: Background In the NEAT022 trial, virologically suppressed persons with HIV at high cardiovascular risk switching from protease inhibitors to dolutegravir either immediately (DTG-I) or after 48 weeks (DTG-D) showed non-inferior virological suppression and significant lipid and CVD risk reductions on switching to dolutegravir relative to continuing protease inhibitors. Methods Post-hoc analysis. Major endpoints were 48-week and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We observed that patients receiving DTG-based regimens were more likely to transition from normal to overweight and observed a significant proportion from transitioning from overweight to obese within the 6-month follow-up period. These results highlight the importance of ongoing monitoring of patients receiving DTG regimens, as there may be implications for increased mortality due to non-communicable diseases among individuals receiving DTG-based treatment [ 10 , 12 , 20 ]. The transition to higher BMI categories among patients receiving DTG-based regimens emphasizes the need for comprehensive healthcare interventions that address not only HIV treatment but also management of associated comorbidities [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that patients receiving DTG-based regimens were more likely to transition from normal to overweight and observed a significant proportion from transitioning from overweight to obese within the 6-month follow-up period. These results highlight the importance of ongoing monitoring of patients receiving DTG regimens, as there may be implications for increased mortality due to non-communicable diseases among individuals receiving DTG-based treatment [ 10 , 12 , 20 ]. The transition to higher BMI categories among patients receiving DTG-based regimens emphasizes the need for comprehensive healthcare interventions that address not only HIV treatment but also management of associated comorbidities [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Switching from tenofovir disoproxil fumarate (TDF) to TAF has also been associated with significant weight gain in PLWH. 316,317 One of the proposed mechanisms of weight gain is due to the reduction of plasma HIV RNA levels and mitigating the catabolic effects associated with viremia; therefore, a restorative process leading to improved health occurs. As a result, some individuals experience weight gain that exceeds normal, healthy levels.…”
Section: Impact Of Art On Cvdmentioning
confidence: 99%
“…Numerous observational studies, retrospective analyses, and large randomized clinical trials have suggested that INSTIs, particularly DTG and BIC, may be associated with more weight gain compared to other ARVs. Within the INSTI class, previous studies have observed varying patterns of weight gain [41,43,[60][61][62][63][64][65][66][67]]. An early study exploring differences in weight gain between INSTIs and other ARVs was the STARTMRK study.…”
Section: The Effect Of Integrase Inhibitors On Weightmentioning
confidence: 99%